Intelligence Sharing: The Challenges among the Nigerian Security Agencies and Government - Bodunde, David Oluwafemi; Balogun, Noah Opeyemi (African Journal of Stability and Development (AJSD), 2018)
Nigeria is a pluralistic society with diverse cultures and with the antecedent of criminal and insecurity activities. However, Nigeria’s government with a view to promoting national security has established many security outfits to cater for national security. For security to thrive in such situation there is need for intelligence sharing among these security agencies. Surprisingly, the multiple security outfits instead of achieving the utmost security among all odds have had to struggle with lack of cooperation, ego boosting, favouritism, and marginalisation. Individual outfit keeps its intelligence gathered within itself with a view to promoting unnecessary relevance and competition among other outfits rather than sharing intelligence to achieve common purpose. The study therefore examines the challenges of intelligence sharing among the Nigerian security agencies and the government that ought to execute intelligence report shared with it. Ironically, the politicisation of intelligence shared with government itself makes a mockery of intelligence sharing among the security outfits. The study also rests on observation and literature on intelligence and security highlighting the challenges of security outfits in Nigeria with their overlapping functions. The paper therefore recommends collaborative effort in intelligence sharing between the security agencies and government, depoliticising intelligence and more provision of security facilities to help gather information timely in order to forestall impending dangers.